2020
DOI: 10.5380/rf.v50i2.62987
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Native Forest Species in Riparian Recovery Forest in the Piauitinga River, Sergipe, Brazil.

Abstract: The riparian forests of the Piauitinga river Basin, Sergipe state, Brazil, are severely degraded, requiring urgent actions aimed their recovery. In this way, the present work was carried out with the objective of analyzing the establishment of native forest species, implanted in a degraded section of riparian forest of the Piauitinga river, in the municipality of Lagarto state of Sergipe, aiming the forest recovery of this area. It was performed the planting of five native forest species, including pioneers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…Gonçalves et al (2012) reported that Genipa spruceana is considered a pioneer specie and usually requires low nutrient availability for its development. Thus, it is a desirable species for recovering degraded areas, mainly in riparian forests (Gama et al, 2020). Gonçalves et al (2002) also affirm that adequate stem diameter for good-quality seedlings is between 5 and 10 mm for native forest species.…”
Section: Resultsmentioning
confidence: 97%
“…Gonçalves et al (2012) reported that Genipa spruceana is considered a pioneer specie and usually requires low nutrient availability for its development. Thus, it is a desirable species for recovering degraded areas, mainly in riparian forests (Gama et al, 2020). Gonçalves et al (2002) also affirm that adequate stem diameter for good-quality seedlings is between 5 and 10 mm for native forest species.…”
Section: Resultsmentioning
confidence: 97%
“…Da mesma forma, Gama et al (2020), ao final de 630 dias de avaliação, encontraram taxa de crescimento em altura de 452,1% em Tapirira guianensis Aubl e 280,6% em Guazuma ulmifolia Lam., entre as espécies estudadas.…”
Section: Discussõesunclassified